Impact of Sales Promotion on Consumer Buying Behaviour - Nath, Soma (International Journal of Engineering and Management Research, 2023)
Sales promotional tools are one of the most important marketing strategies used by producers/ marketers to attract the correct segment of individuals towards their product and create the right consumer segment. This study analyzes the impact of sales promotion tools on consumer buying behaviour in a competitive market. Using a structured questionnaire, it examines how techniques like discounts and offers influence purchase decisions. Findings reveal that price incentives significantly affect consumers, especially budget-conscious buyers. Promotional tools benefit both consumers through cost savings and marketers through increased sales, though overuse may have drawbacks. The study highlights the dynamic nature of consumer preferences and the role of promotions in shaping behaviour.